Evaluación del uso de fibras lignocelulósicas para el reforzamiento de espumas de poliuretano a nivel laboratorio (2018)
In the present work, different natural fibers of lignocellulosic origin were evaluated to be incorporated in rigid polyurethane foams as partial replacement of the commercial polyol used in the production of these, fibers were incorporated at 5%, 10% and 15%. Three types of fibers were analyzed, two of them, mango peel and rice husk, two residues that are generated in large quantities in the country; and microcrystalline cellulose. In this study, properties such as bulk density, water absorption and tensile strength were evaluated, showing that in all prepared samples these three properties are improved with the increase of the OH replacement percentage. It was determinated that the fiber with the best results were the samples with rice husk, finding a percentage of OH replacement of 15% an increase and improvement in properties such as bulk density and tensile strength, for bulk density a value of 33 kg / m3 and for the tensile strength a value of 152.92 kPa. In the case of water absorption, the fiber with the highest yield was the mango peel, reaching up to 277% increase in mass per humidity in the sample prepared with 15% OH replacement.